Repeated and extensive exposure to online terrorist content: counter-terrorism internet referral unit perceived stresses and strategies - Reeve, Zoey (Taylor & Francis, 2020)
U.K. Metropolitan Police Counter-Terrorism Internet Referral Unit (CTIRU) Case Officers (COs) are tasked with identifying, and facilitating the removal of material that breaches the Terrorism Act 2006. COs are extensively and repeatedly exposed to material deemed illegal and harmful (including but not restricted to graphic terrorist and non-terrorist material). However, there is little research on the impact of this work, or how COs manage and mitigate the risks of their roles. Semi-structured interviews reveal the adaptive coping mechanisms that promote good perceived health and wellbeing in CTIRU, as well as areas of concern and improvement.
Keywords: CTIRU; Internet Child Exploitation (ICE); Terrorism